Província alcalina de Fortaleza, Ceará, Brasil: Petrografia, Geoquímica e potencial como remineralizador de solos - Aquino, Jaqueline Mesquita de (2019)
The recent discovery of the subsurface basanite of Fortaleza, restored the interest in the magmatism of the Fortaleza Alkaline Province, because of its genetic relation with the volcanism of the Fernando de Noronha archipelago, and because the occurrences of mafic volcanics were not well documented for this event. This research does a reassessment of the extension of the province and evaluates the potential of the volcanic rock for stonemeal proposes. The Extent of the Fortaleza Alkaline Province was re-evaluated based on the interpretation of a ternary composition of gamma-spectrometric data, petrographic analyzes and whole-rock geochemistry. A total of five alkaline bodies were identified in addition to those which were already mapped. This igneous event is characterized by intrusions and extrusions which are strongly sodic, silica-subsaturated rocks, containing modal and/or normative nepheline, besides rare sodalite. The felsic rocks are mainly constituted by aphyric to glomeroporphyritic phonolites, often with trachytic texture, whereas the mafic members described vary from microporphyritic to glomeroporphyritic basanites, identified mainly in the region of Caucaia, as small dikes that cut the Proterozoic rocks of the Ceará Complex. Additionally, a nepheline syenite and a volcanoclastic breccia were identified in the Tucunduba region, both of which were not mapped in previous works. For the stonemeal proposes, three lithotypes were tested through leaching tests with acid extraction and laboratory incubation test. The volcanoclastic breccia stands out mainly as a natural source of the micronutrient Mn, while the phonolites are not useful for agricultural management because of the sodic character.